Smooth imploding solutions for 3D compressible fluids - Tristan Buckmaster; Gonzalo Cao-Labora; Javier Gómez-Serrano (Forum of Mathematics, Pi)
Building upon the pioneering work of Merle, Raphaël, Rodnianski and Szeftel [67, 68, 69], we construct exact, smooth self-similar imploding solutions to the 3D isentropic compressible Euler equations for ideal gases for all adiabatic exponents